2020
DOI: 10.1002/ps.5995
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of flupyradifurone resistance in the whitefly Bemisia tabaci Mediterranean (Q biotype)

Abstract: BACKGROUND: Bemisia tabaci is one of most notorious pests on various crops worldwide and many populations show high resistance to different types of insecticides. Flupyradifurone is a novel insecticide against sucking pests. B. tabaci resistance to flupyradifurone has been detected in the field, however the mechanism of flupyradifurone resistance has rarely been studied. RESULTS: The flupyradifurone-resistant strain (FLU-SEL) was selected from the susceptible strain of B. tabaci (MED-S) using flupyradifurone f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 45 publications
2
25
0
1
Order By: Relevance
“…This study concerns the natural occurrence of whitefly secondary symbionts and the fitness costs/benefits associated with their infections in the B. tabaci whitefly, focusing on the invasive MED species, which is one group of notorious agricultural pests worldwide having developed high resistance to insecticide ( Wang et al, 2020a , b ). The MED whiteflies includes four phylogenetic clades Q1, Q2, Q3, and ASL, and Q1 is the most widely distributed genotype in most regions, especially in China ( Chu et al, 2008 ; Gueguen et al, 2010 ; Gauthier et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…This study concerns the natural occurrence of whitefly secondary symbionts and the fitness costs/benefits associated with their infections in the B. tabaci whitefly, focusing on the invasive MED species, which is one group of notorious agricultural pests worldwide having developed high resistance to insecticide ( Wang et al, 2020a , b ). The MED whiteflies includes four phylogenetic clades Q1, Q2, Q3, and ASL, and Q1 is the most widely distributed genotype in most regions, especially in China ( Chu et al, 2008 ; Gueguen et al, 2010 ; Gauthier et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The resistance levels were low in a heterozygous Drosophila strain (RFs of 1.9, 1.3 and 4.3, respectively). Finally, metabolic resistance to flupyradifurone, mediated by glutathione‐S‐transferase and P450 monooxygenase, recently was suggested for a Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) resistant strain from China 26 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, RNA interference (RNAi)-based studies have identified several cases of insecticide resistance involving P450s. For example, CYP6CX4 is connected with the resistance to flupyrrolidone in Bemisia tabaci [25]; CYP6CY14, CYP6DC1, and CYP6CZ1 are associated with Aphis gossypii resistance to acetamiprid [26]; CYP321A8, CYP321A9, and CYP321B1 are responsible for Spodoptera frugiperda resistance to chlorantraniliprole [27]. In Drosophila melanogaster, Cyp4g1, Cyp6g1, and Cyp12d1 play major roles in reducing DDT sensitivity [28].…”
Section: P450-mediated Insecticide Resistancementioning
confidence: 99%